2008
DOI: 10.1152/ajpheart.00240.2008
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced inhibition of vascular endothelial cell functions: a role for VacA-dependent nitric oxide reduction

Abstract: Epidemiological and clinical studies provide compelling support for a causal relationship between Helicobacter pylori infection and endothelial dysfunction, leading to vascular diseases. However, clear biochemical evidence for this association is limited. In the present study, we have conducted a comprehensive investigation of endothelial injury in bovine aortic endothelial cells (BAECs) induced by H. pylori-conditioned medium (HPCM) prepared from H. pylori 60190 [vacuolating cytotoxin A (Vac(+))]. BAECs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…All samples not used immediately were stored at −80°C until required. For the purpose of bacterial adhesion assays described above, HAECs and BAECs, cultured as previously described (Martin et al, ; Tobin et al, ), were also examined in parallel with HBMvECs. It can also be noted that bacterial adhesion was examined using both static and sheared endothelial cells (0 versus 10 dynes/cm 2 ), with steady non‐pulsatile shear applied by orbital rotation as previously described by Colgan et al ().…”
Section: Methodsmentioning
confidence: 99%
“…All samples not used immediately were stored at −80°C until required. For the purpose of bacterial adhesion assays described above, HAECs and BAECs, cultured as previously described (Martin et al, ; Tobin et al, ), were also examined in parallel with HBMvECs. It can also be noted that bacterial adhesion was examined using both static and sheared endothelial cells (0 versus 10 dynes/cm 2 ), with steady non‐pulsatile shear applied by orbital rotation as previously described by Colgan et al ().…”
Section: Methodsmentioning
confidence: 99%
“…There are several possible mechanisms underlying the potential causative role of H. pylori in endothelial dysfunction. First, in vitro studies have revealed that H. pylori-induced endothelial dysfunction may be attributed to VacA 58) , an H. pylori-secreted virulence factor that elicits its effects by modulating plasma and ber of epidemiological studies have investigated the association between H. pylori infection and atherosclerosis and its complications based on the "infection hypothesis." From the pathogenic point of view, chronic H. pylori infection contributes to the initiation and development of atherosclerosis through a variety of mechanisms ( Table 2).…”
Section: Potential Mechanisms Through Which H Pylori May Contribute mentioning
confidence: 99%
“…There are some proposed mechanisms for the role of H. pylori infection in the development of atherosclerosis. Endothelial dysfunction is one of them and is attributed to vacA and also to the nutritional effect of this microorganism, which usually results in the malabsorption of folate and the vitamins B6 and B 12 and also hyperhomocysteinemia, which is toxic to endothelial cells (41,42).…”
Section: Discussionmentioning
confidence: 99%